Potencial da nanofibrila lignocelulósica do bagaço de cana-de-açúcar como reforço em filmes de amido - Matos, Thayrine Silva (2022)
In the present work, sugar cane bagasse pulps from the acid hydrolysis process followed by alkaline treatment were used. Part of the material was bleached using H2O2 and NaOH and the other remained with residual lignin. Next, nanofibrils of the lignocellulosic material (NFC) were produced from the mechanical fibrillation process. The nanofibrils produced from the bleached pulp (NFC - B) and the pulp with residual lignin (NFC - NB), were added with percentages of 10, 20, 30 and 50% to a filmogenic solution of 2.5% in starch solids. The addition of unbleached NFC promoted an average increase in tensile strength and modulus of elasticity values, especially for the films with higher percentages of NFC (30% and 50%), with values of 13.36 and 15.49 Mpa and 356.15 and 487 Mpa, respectively. This indicates an increase in stiffness and decrease in elasticity, as the elongation values decreased with increasing amount of NFC. The contact angle values increased with the addition of NFC, classifying all nanofibrillar films as hydrophobic (>90°), except films with 30% NFC - NB and 50% - NB that showed a significant decrease with values of 86° and 83°, respectively. The samples with 50% NFC - NB and B, showed low water vapor permeability (2.17 g.mm/Kpa-¹ day-¹ m²), indicating that the films have a good vapor barrier. The transparency results for the films with 30% and 50% NFC - NB, although not significant, showed higher values of transmittance, indicating greater transparency. Although for the other treatments the influence of residual lignin on the test results was not identified, the addition of 30-50% NFC - NB from sugarcane bagasse were the percentages with the best results for strengthening the structure and improving the barrier properties of the cassava starch based films.